2022
DOI: 10.1111/cpr.13351
|View full text |Cite
|
Sign up to set email alerts
|

Mesentery AjFGF4–AjFGFR2–ERK pathway modulates intestinal regeneration via targeting cell cycle in echinoderms

Abstract: Objectives:The purpose of the study aims to understand the regeneration process and its cytology mechanism in economic echinoderms. Materials and Methods:The intestine regeneration process of Apostichopus japonicus was investigated by immunohistochemistry and the cell proliferation was detected by immunofluorescence and flow cytometry. Fibroblast growth factor 4 of A. japonicus (AjFGF4) was screened by RNA-seq analysis and validated to regulate cell proliferation by siAjFGF4 and recombinant-AjFGF4 treatment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
(127 reference statements)
0
9
0
Order By: Relevance
“…For instance, like the blastema cells of the amphibians, the cells of the holothurian anlage coelomic epithelium are proliferative undifferentiated cells and originated via a dedifferentiation process. Moreover, some of the genes expressed by the amphibian blastema cells or the overlying AEC, such as Wnt, Tgf-beta, and Fgf, are also known to be expressed during sea cucumber regeneration (Auger et al, 2023; Zeng et al, 2023). In amphibians, some of these factors are thought to be released by cells of the AEC, serving as a way of modulating the blastema cell activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, like the blastema cells of the amphibians, the cells of the holothurian anlage coelomic epithelium are proliferative undifferentiated cells and originated via a dedifferentiation process. Moreover, some of the genes expressed by the amphibian blastema cells or the overlying AEC, such as Wnt, Tgf-beta, and Fgf, are also known to be expressed during sea cucumber regeneration (Auger et al, 2023; Zeng et al, 2023). In amphibians, some of these factors are thought to be released by cells of the AEC, serving as a way of modulating the blastema cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…This expression of Fgf and Wnt and their possible functions correlates with what has been found in sea cucumbers. Not only are the same growth factors expressed in C1 and C3, but a recent study highlighted the role of FGF4 as a modulator of cell proliferation during the intestinal regeneration of the sea cucumber A. japonicus (Zeng et al, 2023). This group demonstrated that inhibiting FGF4 and its receptor, FGFR2, negatively affected cell proliferation of the mesothelial layer during intestinal regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The sea cucumber, A. japonicus, as a nonmodel organism, is challenging to study with respect to its metabolic activity and signal transduction. Considering the high transfection efficiency, rapid proliferation, and evolutionarily conserved proteins in cell-signaling pathways in model cell lines [ 55 ], and the wide use of HEK293 cell lines in cell-signaling studies in invertebrates [ 56 , 57 , 58 ], we chose to use transfected HEK293 cells to determine the molecular and functional characteristics of AjGPER1. The limitations of studying sea cucumber GPER1 outside of its evolutionary context, to some extent, were complemented by in vitro experimental data from cultured A. japonicus ovarian tissues highly expressing this gene.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of high-throughput sequencing technology, a largescale gene expression profile related to the regeneration process of sea cucumbers has been constructed, enabling the study of this mechanism at the global transcriptome and proteome levels. The transcriptome of Apostichopus japonicus (A. japonicus) during intestinal regeneration has been well studied, while proteomic analysis only reported at the normal intestine and the early stage of regeneration (3 days post-evisceration (dpe)) [15,16]. Given that the process of intestinal regeneration is divided into multiple stages, and each process is crucial for regenerating a complete intestine and involves a series of cellular events, we investigated the differential proteins of the entire process of intestinal regeneration using tandem mass tag (TMT)-based proteomics.…”
Section: Introductionmentioning
confidence: 99%